EXPLORING THE RESEARCH JOURNEY: BARRIERS AND FACILITATORS FOR POSTGRADUATE MAXILLOFACIAL TRAINEES - Fahimuddin; Khan, Naveed Afzal; Khan, Muslim; Kayani, Harmain; Durrani, Mushyyada; Zakariya, Muhammad (Khyber Journal of Medical Sciences, 2025)
Objective: To explore the Barriers and Facilitators for research in Postgraduate Maxillofacial Trainees. Methodology: Exploratory Qualitative study design (Case study) was adopted. A ten-question questionnaire was developed and piloted to identify the different perceptions of maxillofacial Trainees. Purposive Sampling was used to conduct eight semi-structured interviews. Thematic analysis was undertaken with Triangulation of transcripts. Results: Five main themes emerged from the data analyses. Research as a Path to Innovation showed research as a means of pushing boundaries and advancing knowledge. Motivation to Make a Difference outlined that the motivation for conducting research stems from personal passion and external pressures. Hurdles on the Research Path portrays the barriers in the research journey. Fueling Research Success highlights the facilitators in this journey. Nurturing Research Skills for Tomorrow shows the path to improve research skills among trainees. Conclusion: Maxillofacial surgery residents face significant barriers in their research journey. Despite these obstacles, their intrinsic motivation and the requirement for academic publishing drive their research efforts. To improve research outcomes, early exposure to research, continuous training, and institutional support are essential.